Perencanaan Dan Perancangan Pasar Seni Tradisional Dengan Fasilitas Creative Hub Di Gianyar, Bali. - I Made Ari Saputra Ari Saputra; I Gede Surya Darmawan; Agus Kurniawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
The traditional art market is part of the supporting facilities for the tourism sector. In its role, the traditional art market acts as a forum for UKM to play a role in the trading industry. The traditional art market is a traditional market whose commodities sell handicraft goods from UKM with the sales method applying the traditional system, namely by bargaining. Gianyar Regency, Bali has potential in the industrial, tourism and trade sectors. Based on the results of observations on the development of facilities, the convenience and arrangement of stall and traders are not so good that it affects the convenience of visitors, plus the development of modern souvenir shops, it can be seen from the decreasing interest of visitors from the traditional art market. As a traditional art market where UKM take shelter, it is necessary to develop the potential of UKM and artists in traditional art markets, restore the comfort and interest of visitors in the art market, and provide good facilities in its future development, a new idea and design is needed, namely an art market that has Facilities that can develop the potential of UKM and local artists are the Art Market which is equipped with Creative Hub facilities and applies architecture that is close to art itself, adaptive and dynamic architectural designs to time and conditions.